Estimating the Rainfall Patterns in Namibia: Are rainfall patterns a myth or fact? - Sartorius, H.J.; Kalundu, K.M (Namibian Journal for Research, Science and Technology, 2020)
Rainfall is generally regarded as the key driver for ecosystem processes, particularly important within the dynamics of semi-arid regions. Since the precipitation impacts the natural environment, human society and the economy, the paper applied rainfall forecasting to avail early warning patterns. The Waterberg rainfall data from 1895 to 2019 was used to determine a better understanding of its pattern. This is necessitated because knowledge of rainfall patterns are required for reviewing production targets and a necessity for decision making in agriculture. Data shows that only 34% of the rainfall years accounted average rainfall, meanwhile 66% of rainfall years is either classified as above or below. Further, results show that the ENSO patterns follow a cyclical pattern, which corresponds to the local Waterberg rainfall. Econometric approaches postulate that thereexists volatility of rainfall, effective rainfall, its intensity, cycles and the ENSO data. This paper shows that rainfall forecasting is possible when using a model that takes into account the variation in the ENSO, cyclical pattern and the accumulation of various rainfall cycles. A five year forecast shows that the current experienced drought cycle is coming to an end, and that the prospects of above average years will only persist for 2 years. We recommend that knowledge of the cyclical trend needs to be translated into reliable periodic statements to safeguard Namibia against future famines, possible food shortages and counter rising food prices. Although the methods are robust, they call for further research into the causes of dynamics of observed rainfall variability.